Vulnerability indicators to conditions of water deficit in the mango production system (Semiárida, 2020)
Climate change has its causes in social facts, mitigation or adaptation strategies must start from the same society. The reduction of the vulnerability of agricultural production systems occurs through the implementation of technologies that take into account the combination of productive, social, economic and environmental factors. The cultivation of mango (varieties Tommy, Keitt, Hilacha) is of great importance and tradition in the municipality of Anapoima, Colombia. It was carried out with an analysis of the vulnerability of the mango system to water deficit events based on the productive and socioeconomic conditions of the producers. There is a moderate sensitivity of the crop and low capacity of adaptation of the producers before a scenario of water deficit. The technologies that could reduce vulnerability are floral induction, fertilization and phytosanitary management practices, which are complementary and should be implemented jointly. For this purpose, credit may be accessed and strategies established for the collection and conservation of water sources that allow access to the water resource.
Keywords: climate change; adaptation; irrigation; resilience